Separation with the aid of surface and interfacial tensions - Arato, E. G. (Cranfield University, 1984)
The investigations described in this thesis were aimed at developing or laying the foundation of novel techniques of liquid/solid and liquid/liquid separation by utilising the capillary effect. In Part I the studies related to the extraction of water from an agglomerate of particulate solids and water (i. e. dewatering) by means of ceramic elements are described. These studies clearly showed that although water can be extracted from the agglomerate by ceramic elements and evaporated to atmosphere, the rate of extraction is generally too low for commercial application of the technique. Part II of this thesis deals with the separation of two immiscible liquids (i. e. water and oil) using a ceramic filter tube either as a 'threshold pressure' separator or a coalescer. It was found that diesel fuel, for instance, could be separated to practically 100% efficiency from a secondary dispersion of oil/water, provided the applied pressure across the tube is maintained below a critical value. This technique could form the basis of a very efficient commercial oil/water separator.